UPAYA PEJABAT PUBLIK MENSOSIALISASIKAN UNDANG-UNDANG NOMOR 16 TAHUN 2006 SEBAGAI PAYUNG HUKUM REVITALISASI PENYULUHAN PERTANIAN DI KOTA PAGAR ALAM - Novi Apriani (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2020)
The objective of this study was to find out the efforts and the target of public officials to socialize the Constitution Number 16 of 2006 as the legal protection for agricultural extension revitalization in Pagar Alam. This study was conducted in Pagaralam, South Sumatra Province in December 2018 until February 2019, the research method was Case Study method, for sampling method used Purposive Sampling and Accidental Sampling method. The data collection methods in this study were participant observation and indepth interviews to the respondents who have been determined by using quisionary aids that have been prepared previously. The data processing was conducted by using deseriptive-qualitative method. From the results of the research, it showed the effort that has been done to socialize Constitution Number 16 of 2006 about agricultural, tishezy and forestry extension systems as the legal protection for Agricultural Extension Revitalization in Pagar Alam and to socialize and in socializing it to members of farmer groups, agricultural extension agents invite farmers in extension activities. Meanwhile, the farming communities carried out in plaques, banners and even through social media. Then the target socialization of Constitution Number 16 of 2006 about agricultural, fisheries and forestry extension systems as a legal protection for Agricultural Extension Revitalization were agricultural extension and farmers.